Eksistensi Lagu Islami Dalam Pendidikan Anak Usia Dini - Giardi, Lesta Yahsa; Hanifah, Ridhani Nur; Icshan, Yazida (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2022)
Islamic education iIslamic education is defined as the process of transferring learning knowledge that is conveyed to students by educators and can grow and develop the potential of students to achieve life goals. To take advantage of the golden age of PAUD, educators adopt inspiring and fun learning methods, namely block play, memorization, role-playing, card games, experimentation, singing, and playing music. The method used in this research is qualitative method. The type of qualitative research used by the researcher is a case study, which is an in-depth exploration of a case, collecting comprehensive information using different data collection procedures based on time estimates. Childhood usually begins with parents sending them to PAUD, so it is not surprising that they enter higher schools. In PAUD schools, singing is often taught because children can have fun and will understand the songs taught by educators. Learning through play can shape children's character and realize all their teachings, including morals. Islamic songs are the result of innovative learning methods, the use of very relevant Islamic songs is used as an effort to optimize character formation in students. The Islamic song learning system is flexible and unlimited because it is done together in a fun atmosphere and many children enjoy learning activities such as singing, clapping, body expressions and other activities.s defined as the process of transferring learning knowledge that is conveyed to students by educators and can grow and develop the potential of students to achieve life goals. To take advantage of the golden age of PAUD, educators adopt inspiring and fun learning methods, namely block play, memorization, role-playing, card games, experimentation, singing, and playing music. The method used in this research is qualitative method. The type of qualitative research used by the researcher is a case study, which is an in-depth exploration of a case, collecting comprehensive information using different data collection procedures based on time estimates. Childhood usually begins with parents sending them to PAUD, so it is not surprising that they enter higher schools. In PAUD schools, singing is often taught because children can have fun and will understand the songs taught by educators. Learning through play can shape children's character and realize all their teachings, including morals. Islamic songs are the result of innovative learning methods, the use of very relevant Islamic songs is used as an effort to optimize character formation in students. The Islamic song learning system is flexible and unlimited because it is done together in a fun atmosphere and many children enjoy learning activities such as singing, clapping, body expressions and other activities. Abstrak : Pendidikan Islam didefinisikan sebagai proses transfer ilmu pembelajaran yang disampaikan kepada peserta didik oleh pendidik serta dapat menumbuhkan dan meningkatkan bakat peserta didik dalam memenuhi tujuan kehidupan. Untuk menmqmfaatkan masa keemasan PAUD, pendidik mengadopsi metode pembelajaran yang inspiratif dan menyenangkan yaitu block play, hafalan, role-playing, card play, eksperimentasi, bernyanyi, dan bermain musik. Metode yang digunakan oleh penelitian ini yaitu metode kualitatif. Studi kasus merupakan jenis penelitian yang digunakan, yaitu eksplorasi mendalam tentang suatu kasus, mengumpulkan informasi yang komprehensif dengan menggunakan prosedur pengumpulan data yang berbeda berdasarkan perkiraan waktu. Masa kanak-kanak biasanya dimulai dengan orang tua menyekolahkan mereka ke Pendidikan Anak Usia Dini, sehingga tidak kaget jika mereka masuk ke sekolah yang lebih tinggi. Di sekolah Pendidikan anak usia dini, metode yang sering diberikan kepada peserta didik yaitu menyanyi, karena anak usia dini lebih bersenang-senang dan dengan mudah memahaminya. Belajar melalui bermain dapat membentuk karakter anak dan mewujudkan segala ajarannya, termasuk akhlak. Lagu islami merupakan hasil dari metode pembelajaran yang inovatif, penggunaan lagu islami yang sangat relevan digunakan sebagai upaya untuk mengoptimalkan pembentukan karakter pada siswa. Sistem pembelajaran lagu Islami bersifat fleksibel dan tidak terbatas karena dilakukan secara bersama-sama dalam suasana yang menyenangkan dan banyak anak yang menikmati kegiatan belajar seperti menyanyi, tepuk tangan, ekspresi tubuh dan aktivitas lainnya.